Pembiasaan Membaca Al-Qur'an dengan Metode Iqro di MTs Hasanah Fathimiyah Cikarang Barat - Ami Indriani; Ajat Rukajat; Khalid Ramdhani (ISLAMIKA, 2022)
This research discusses the Efforts of Islamic Religious Education Teachers in Improving the Quality of Reading Al-Quran at MTs Hasanah Fathimiyah, West Cikarang. This research is motivated by the lack of students' interest in reading the Koran. The problem can be seen that in the process of learning the Qur'an, there are still students who are less serious, do not do assignments, do not pay attention when the teacher explains, speak unkindly / say impolitely. This research includes qualitative research with a case study approach with the aim of presenting situations, activities or social behavior in detail and accurately. This research data collection was done by means of interviews, observation, and documentation. While the data analysis techniques were obtained through data reduction, data presentation and data inference. The researcher found that the efforts of Islamic Religious Education teachers in improving the quality of reading the Al-Quran for students at MTs Hasanah Fathimiyah Cikarang Barat include: through habituation of the use of the Al-Quran before class starts, providing funding facilities for parent-student cooperation, assignment activities, and building good relationships with students. The method used by teachers in improving the quality of students' reading the Koran is by using various methods, namely the aiqro' method, the qira'ati method, and the Jibril method. Factors supporting and inhibiting Islamic Religious Education teachers in improving the quality of reading the Al-Quran for students include: supporting factors, namely from the innate nature of each student outside of school, the availability of supporting facilities. While the inhibiting factors are the lack of student interest in learning the Koran, the lack of parental support for their children, and limited time.